Bi-fluctuation in Na0.5Bi0.5TiO3 ferroelectric ceramics with abnormal relaxor behaviour. Issue 21 (2nd November 2019) - Luo, Huijiadai; Ke, Hua; Zhang, Hongjun; Zhang, Liwei; Li, Fangzhe; Cao, Lu; Guo, Pengkang; Jia, Dechang; Zhou, Yu
ABSTRACT: The existence of Bi-fluctuation dispersing in Na0.5 Bi0.5 TiO3 (NBT) relaxor ferroelectric is hinted in other recent studies. However, this fluctuation has not been directly observed yet. We introduce the Bi-rich nano-regions with different sizes in a series of NBT ceramics by the slight excess of Bi 3+ content. The crystal symmetries of the Bi-rich nano-regions and the NBT matrix are rhombohedral. The lattice parameters of the nano-regions are larger than those of the matrix in NBT ceramics, which were confirmed by the X-ray diffraction Rietveld refinement, TEM techniques and first-principles calculation. Also, the disorder-induced nano-regions appearing as Bi-fluctuation are associated with the complex phase transitions and the high-frequency relaxor behaviour of NBT suggested by the dielectric measurements and Raman spectra.